Sustainable Development Path of Post-Project Evaluation: New Quality Productivity Perspective - Zhao , Jiufeng; Liu, Sihui (Transformations In Business & Economics, 2025)
The introduction of the concept of new quality productivity in 2023 has precipitated a wave of extensive reforms in various industries. The efficient integration of new quality productivity measures within the context of the new era has become a significant challenge in achieving industry development. Drawing upon the paradigm of new quality productivity, this paper employs the CiteSpace and bibliometric mapping visualisation and analysis methodologies to explore the sustainable development trajectory of post-evaluation of engineering projects. This provides a theoretical foundation and practical recommendations for the sustainable development of engineering projects.
Keywords: new quality productivity; post-project evaluation; CiteSpace; bibliometric mapping